Reactive power tracing in pool-based power system utilising the hybrid genetic algorithm and least squares support vector machine - Mohd Wazir, Mustafa, Prof. Dr.; Mohd Herwan, Sulaiman; Hussain, Shareef, Dr.; Siti Nur Hidayah, Abd Khalid (The Institution of Engineering and Technology, 2013)
Link to publisher's homepage at http://www.theiet.org